Increasing the Efficiency of Diagnostics in the Brush-Commutator Assembly of a Direct Current Electric Motor; Energies; Vol. 17, iss. 1 - Filina O. A. Olga Alekseevna; Martyushev N. V. Nikita Vladimirovich; Malozemov B. V. Boris Vitaljevich; Tynchenko V. S. Vadim Sergeevich; Kukartsev V. A. Viktor Alekseevich; Bashmur K. A. Kirill Aleksandrovich; Pavlov P. P. Pavel Pavlovich; Panfilova T. A. Tatjyana Aleksandrovna (2024, 2024)
Title screen